Moderators of job-search intensity, self-esteem and career decision-making. - Abdullah, Norida; Ninggal, Mohd Tajuddin (Sekolah Psikologi dan Kerja Sosial universiti malaysia Sabah, 2010)
This study examined the relationship and differences between job-search intensity, self-esteem and career decision-making self-efficacy among students. The moderators variables studied in this research were gender, academic performance and academic programs. Quantitative method used was correlation research. The data were collected from a self-reported questionnaire to 304 graduating students of a public university in Malaysia. Participants were recruited using cluster sampling procedure, also known as multistage sampling. The statistical tests used to analyzed the data were Pearson correlation (r) at 0.01 significant level, t-test and ANOVA at the 0.05 significant level. The finding showed that there are a significant relationship between job-search intensity, self-esteem and career decision-making self-efficacy. The results also show that gender had significant influenced for self-esteem and career decision making self-efficacy. Academic performance (CGPA) influenced job-search intensity and academic programs (faculty) also influenced job-search intensity, self-esteem and career decision-making self-efficacy. The implications for students' developments and career development centre are discussed.